Caracterização geofísica do ambiente carstico da caverna Furna Feia (Baraúna/RN) e do complexo de cavernas Toca da Boa Vista (Lajes dos Negros/BA) - Rodrigues, Rafael Saraiva (2020)
karst features can contribute to a better understanding of the behavior of fluids in these important reservoir, since they can function as flow barriers, ducts or even as reservoirs. Within this context, the caves of Furna Feia, located in the municipality of Baraúnas / RN in the carbonates of the Jandaíra Formation in the Potiguar Basin and Toca da Boa Vista, located in the community of Lajes dos Negros, in the municipality of Campo Formoso, carbonates from the Salitre Formation in the Irecê Basin, were selected for a geophysical characterization of karst features. In this way, the methods of Ground Penetrating Radar (GPR) and Electroresistance (ER), which presented responses with different depths and resolutions. The ER method has a character of recognition, in which the metric resolution allows to identify zones and peaks of different resistivities. While the GPR exhibits a quality of detail, enabling the identification of radarfacies up to the centimeter scale. Although the ER has a lower resolution, this provides data with greater depth, while the depth of GPR investigation is limited by the attenuation of the electromagnetic wave (EM) in the medium, which is directly related to the antenna used and the geological characteristics of the environment under study. The contrasts of resistivity and EM properties, between empty spaces and the less altered embedding rocks are identified, respectively, in the sections geoelectric and radargrams, by areas of high resistivity and by zones of attenuation of the signal EM and, which allow its qualitative and quantitative characterization. The CARACTERISTICS geological characteristics of the investigated area and the target (size and depth) are crucial factors for survey success, as well as the choice of electrode arrangement, the length of the line of research and the signal-to-noise ratio. Therefore, the selected caves were imaged and parameterized, comparing the result with the internal imaging of the obtained with LIDAR. As a result for the Furna Feia cave region, 4 zones of apparent resistivity and two radarfacies with GPR were delimited. It was It is possible to identify a layer with high permeability that can be an analog, in scale outcrop, of the Super-K layers found in the Pre-Salt. An integrated analysis between methods enabled the construction of a conceptual geological model for the formation of this cave. For the cave of Toca da Boa Vista, the GPR method presented a higher correspondence between the interpreted geometry of the cave dome and the geometry obtained with the Laser Scanner. The ERT method showed an excellent result in the identification of hypogenic flow feeding features, in addition to allowing the separation between cavities filled with sediment or air at different depth levels. Both methods corroborate with conceptual models already existing in the literature, in addition to providing a range new information and details on the fragile behavior of the lower layers surface areas affected by collision, fracturing and carstification.